Ifi30 Is Required for Sprouting Angiogenesis During Caudal Vein Plexus Formation in Zebrafish - Wang, Xiaoning; Ge, Xiaojuan; Qin, Yinyin; Liu, Dong; Chen, Changsheng (Frontiers in Physiology, 2022)
Interferon-gamma-inducible protein 30 (IFI30) is a critical enzyme that mainly exists in immune cells and functions in reducing protein disulfide bonds in endocytosis-mediated protein degradation. Regardless of this, it is also found to be expressed in vascular system. However, the functions of IFI30 in vascular development remains unknown. Vascular network formation is a tightly controlled process coordinating a series of cell behaviors, including endothelial cell (EC) sprouting, proliferation, and anastomosis. In this work, we analyzed the function of zebrafish Ifi30, orthologous to the human IFI30, in vascular development during embryogenesis. The ifi30 gene was found to be highly expressed in the caudal vein plexus (CVP) region of zebrafish embryos. Morpholino-mediated Ifi30 knockdown in zebrafish resulted in incomplete CVP formation with reduced loop numbers, area, and width. Further analyses implied that Ifi30 deficiency impaired cell behaviors of both ECs and macrophages, including cell proliferation and migration. Here, we demonstrate a novel role of IFI30, which was originally identified as a lysosomal thiol reductase involved in immune responses, in CVP development during embryogenesis. Our results suggest that Ifi30 is required for sprouting angiogenesis during CVP formation, which may offer an insight into the function of human IFI30 in angiogenesis under physiological or pathological conditions.